Enrichment of 18O in the mantle sources of the Antarctic portion of the Karoo large igneous province - Heinonen, Jussi S.; Luttinen, Arto V.; Whitehouse, M.J. (Contributions to Mineralogy and Petrology, 2018)
Karoo continental flood basalt (CFB) province is known for its highly variable trace element and isotopic composition, often attributed to the involvement of continental lithospheric sources. Here, we report oxygen isotopic compositions measured with secondary ion mass spectrometry for hand-picked olivine phenocrysts from similar to 190 to 180 Ma CFBs and intrusive rocks from Vestfjella, western Dronning Maud Land, that form an Antarctic extension of the Karoo province. The Vestfjella lavas exhibit heterogeneous trace element and radiogenic isotope compositions (e.g., epsilon(Nd) from -16 to +2 at 180 Ma) and the involvement of continental lithospheric mantle and/or crust in their petrogenesis has previously been suggested. Importantly, our sample set also includes rare primitive dikes that have been derived from depleted asthenospheric mantle sources (epsilon(Nd) up to + 8 at 180 Ma). The majority of the oxygen isotopic compositions of the olivines from these dike rocks (delta O-18 = 4.4-5.2%; Fo = 78-92 mol%) are also compatible with such sources. The olivine phenocrysts in the lavas, however, are characterized by notably higher delta O-18 (6.2-7.5%; Fo = 70-88 mol%); and one of the dike samples gives intermediate compositions (5.2-6.1%, Fo = 83-87 mol%) between the other dikes and the CFBs. The oxygen isotopic compositions do not correlate with radiogenic isotope compositions susceptible to crustal assimilation (Sr, Nd, and Pb) or with geochemical indicators of pyroxene-rich mantle sources. Instead, delta O-18 correlates positively with enrichments in large-ion lithophile elements (especially K) and Os-187. We suggest that the oxygen isotopic compositions of the Vestfjella CFB olivines primarily record large-scale subduction-related metasomatism of the sub-Gondwanan mantle (base of the lithosphere or deeper) prior to Karoo magmatism. The overall influence of such sources to Karoo magmatism is not known, but, in addition to continental lithosphere, they may be responsible for some of the geochemical ...